Dynamical characterization of fully nonlinear, nonsmooth, stall fluttering airfoil systems - dos Santos, L. G.P.; Marques, F. D.; Vasconcellos, R. M.G. [UNESP] (Springer Nature, 2022)
Stall flutter is turning into a more likely condition to be encountered as the demand for increasingly more flexible wings grows for HALE-like aircraft. Due to the various nonlinearities involved that can lead to complex motion, the characterization of the dynamical behavior in the post-flutter condition becomes important. The dynamics of a pitch–plunge idealized HALE typical section with aerodynamic, structural and kinematic nonlinearities in the stall flutter regime was investigated using an aeroelastic state-space formulation which includes a modified Beddoes-Leishman dynamic stall model. The results reveal that period-doubling was possible without stall, but chaos arose at discontinuity-induced bifurcations due to dynamic stall. A parametric study has been conducted to assess the influence of key parameters in the development of bifurcations and chaos.
Keywords: Chaos; Discontinuity-induced bifurcations; Dynamic stall; HALE; Piecewise-smooth systems